Assessment of Nurses Implementation of Universal Precautions in the AIDS Wards of Ibn-Zuheir and Ibn- Al- Kahteeb Hospitals - hassan, Huda (Iraqi National Journal of Nursing Specialties, 2005)
A descriptive study was conducted at two Epidemic Hospitals in Baghdad from 1st of August( 2003) to 1st of October (2004) in order to identify the nursing staff working in AIDS word to implementation of universal precautions for patients with AIDS and relation to some variable. The sample is consisted of (50) nurses who are working in AIDS ward in Ibn- Zuheir and Ibn- Al- Kahteeb Hospitals. Instruments consist of (20) items related with demographic characteristics of nurses and universal precautions items . Validity of the instrument was established through a panel of( 4) experts in specific fields . Descriptive and inferential statistics procedure were applied to the data analysis. Results its show that most of nurses was males and they have (16-20) years of experience and there are significant relationship between the implementation of universal precautions and years of experience. The study recommended to planning and implementing specific training programs for nurses in all health institutions about universal precautions.